The effect of epidermal growth factor on brush border surface area and function in the distal remnant following resection in the rabbit. Issue 1 (1st January 1999) - Hardin, J A; Chung, B; O'Loughlin, E V; Gall, D G
Abstract : Background: Epidermal growth factor (EGF) has been shown to increase intestinal absorptive surface area and transport function in normal animals. Aims: To examine the effect of EGF on absorptive surface area and brush border membrane function in a model of massive small bowel resection. Methods: New Zealand white rabbits were randomised into two groups: a resected group (60% proximal small bowel resection); and an unmanipulated control group. Distal remnant tissue was examined 10 and 21 days postsurgery. In separate experiments oral EGF (40 μg/kg/day) was administered to resected animals from days 3 to 8 and animals were studied on day 10. Results: Ten days postsurgery brush border surface area and total absorptive surface area were significantly increased in remnant tissue while brush border membrane vesicle (BBMV) glucose uptake was significantly decreased compared with controls. By 21 days brush border surface area returned to control levels though BBMV glucose uptake remained depressed. EGF treatment induced a further increase in brush border surface area in remnant intestine but did not alter BBMV glucose uptake. Conclusions: Surgical resection results in significant elevations in absorptive surface area coupled with a decrease in brush border membrane transport function distal to the site of anastomosis. EGF enhances glucose uptake in remnant intestine via recruitment of additional microvillus membrane into the brush border.